2006
DOI: 10.20870/oeno-one.2006.40.1.882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abscisic acid in triggering "véraison" in grape berry skins of <em>Vitis vinifera</em> L. cv. Cabernet-Sauvignon

Abstract: <p style="text-align: justify;">Grape berry ripening is characterised by numerous metabolic and physiological changes, placed under hormonal control. The phytohormone abscisic acid (ABA) is considered as a possible promoter of « véraison », since it accumulates at this time. In order to evaluate its impact, we assess the effect of ABA on several parameters of maturity: anthocyanins synthesis, phenylalanine ammonia-lyase activity, sugar contents, acidity and maturity index, both in untreated berry skin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 8 publications
5
29
1
1
Order By: Relevance
“…Merlot during ripening. ABA accumulates during the colour change period, in agreement with other works (Antonin et al, 2003;DaPeng et al 1997;Gagné et al, 2006), suggesting a central role of ABA in triggering veraison and ripening. This accumulation is clearly related to the change of skin coloration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Merlot during ripening. ABA accumulates during the colour change period, in agreement with other works (Antonin et al, 2003;DaPeng et al 1997;Gagné et al, 2006), suggesting a central role of ABA in triggering veraison and ripening. This accumulation is clearly related to the change of skin coloration.…”
Section: Discussionsupporting
confidence: 91%
“…This accumulation is clearly related to the change of skin coloration. In addition of the modifications of ABA contents in the berries, it has been shown by many studies that the change in berry colour and the modifications in the chlorophyll loss were related to the increase in ABA concentration (Gagné et al, 2006;Wang et al, 2005). Our results suggested then that hormonal changes due to the modifications of ABA statues could influence and induced the onset of ripening process.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These results confirmed the finding of earlier studies also where good correlations between ripening of grape berries and accumulation of various transcripts of polygalacturonase, pectin methylesterase, cellulose synthase and expansins were recorded. In addition to this, auxin has been proposed as a negative regulator (Davies et al 1997) while ABA is reported to act as a positive regulator of berry ripening (Gagne et al 2006).…”
Section: Role For Ethylene In Ripening Of Non-climacteric Fruitsmentioning
confidence: 99%
“…Frost events after budbreak or extreme temperatures and precipitation during bloom can cause substantial yield losses by reducing the number and size of fruit clusters [21][22][23]. Fruit yield can also be influenced by management practices such as irrigation strategy [13], canopy manipulation [24], pruning [24], fertilizers [25,26], biostimulants [27][28][29][30][31][32][33][34][35], and rootstock selection [36].…”
Section: List Of Tablesmentioning
confidence: 99%